Association Between Weight Loss and Spontaneous Changes in Physical Inactivity in Overweight/Obese Individuals With Knee Osteoarthritis: An Eight‐Week Prospective Cohort Study. Issue 3 (17th February 2020) - Bartholdy, Cecilie; Christensen, Robin; Kristensen, Lars Erik; Gudbergsen, Henrik; Bliddal, Henning; Overgaard, Anders; Rasmussen, Marianne U.; Henriksen, Marius
Abstract : Objective: To describe spontaneous changes in time spent being physically inactive that is measured continuously by accelerometry during an 8‐week weight‐loss intervention in overweight/obese individuals with knee osteoarthritis (OA). Methods: This study was designed as an observational cohort study including individuals from an OA outpatient clinic who were concomitantly overweight/obese and had symptomatic knee OA. Participants completed an 8‐week dietary intervention that had been previously shown to induce substantial weight loss. The main outcome was accelerometer‐based measurement of daily physical inactivity for 24 hours during the 8‐week intervention period that was presented as change in the average daily time spent inactive (sitting, reclined, or sleeping) from 1 week prior to intervention to the last week of the intervention. Results: A total of 124 participants completed the dietary intervention and had valid accelerometer recordings. The mean weight loss was 12.7 kg (95% confidence interval [95% CI] –13.2, –12.1; P < 0.0001) after 8 weeks, which corresponded to a decrease in body mass index of 4.3 kg/m 2 (95% CI –4.5, –4.2; P < 0.0001). Significant improvements in OA symptoms (assessed by the Knee Injury and Osteoarthritis Outcome Score [KOOS]) was found across all subscales; an improvement of 12.8 points (95% CI 10.6, 15.0; P < 0.0001) was observed for pain using the KOOS. No statistically significant change occurred in the average daily time spent inactive from baseline to follow‐up (mean change 8.8 minutes/day [95% CI –12.1, 29.7]; P = 0.41). Conclusion: Physical inactivity remains stable despite a clinically significant weight loss and improvements in knee OA symptoms. Change in inactivity does not seem to occur spontaneously, suggesting that focused efforts to reduce inactive behaviors are needed.